The comparative analysis of the main indicators of the Baltic states economic development in the conditions of the European integration - Tsaurkubule, Zhanna; Vishnevskaja, Alevtina (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The article examines the ways of three Baltic States development in the context of European integration. It considers some aspects of economy, especially the development and utilization of opportunities of the European market. It also estimates the prospects of foreign direct investment uses and the creation of the most favored environment for business development. It marks the difference in economic management principles, which enabled Estonia to lead the three Baltic countries, and Lithuania to rank second. Insufficient activity of Latvia in the development of those industries that are able to create a product with high added value is noted. The conclusion is drawn that, overall, the prospects for further development of the three Baltic countries are related to ensuring the high quality and productivity, ensuring competitiveness of production and productive transformation of the limited manpower resources
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 466, s. 223-235
Keywords: Baltic countries; foreign direct investment; economic integration; economic development; indicators; FDI; kraje bałtyckie; integracja gospodarcza; rozwój gospodarczy; wskaźniki; bezpośrednie inwestycje zagraniczne; BIZ